Pengaruh Product Quality, Sevice dan Trust terhadap Purchase Intension Online - Andi Yulianto; Roby Setiadi; M. Ajis Susilo (Journal of Economics and Management (JECMA), 2021)
The growing internet makes buying and selling business very promising. Consumers feel the comfort and convenience when shopping online. But this is inseparable with someone's concern when going shopping online. This of course can affect purchase intension online. This study aims to identify the magnitude of the influence of the factors forming consumer behavior, namely product quality, service and trust in purchase intension online. This research was conducted on smartphone users who have shopped online. The samples used were 250 people. The research method used is quantitative. This study uses descriptive analysis techniques and multiple linear regression. The data was analyzed using the SPSS program. The questions in this questionnaire are closely related to product quality, service and trust from the perspective of purchase intension online. The results of the answers to this questionnaire will be calculated to determine how much influence it has on purchase intension online. By knowing the results of this research related to online shopping interest, can understand more deeply about the customer's views on product quality, service and trust and to determine the right strategy.